Deletion of Protocadherin Gamma C3 Induces Phenotypic and Functional Changes in Brain Microvascular Endothelial Cells In Vitro - Gabbert, Lydia; Dilling, Christina; Meybohm, Patrick; Burek, Malgorzata (Frontiers in Pharmacology, 2020)
Inflammation of the central nervous system (CNS) is associated with diseases such as multiple sclerosis, stroke and neurodegenerative diseases. Compromised integrity of the blood-brain barrier (BBB) and increased migration of immune cells into the CNS are the main characteristics of brain inflammation. Clustered protocadherins (Pcdhs) belong to a large family of cadherin-related molecules. Pcdhs are highly expressed in the CNS in neurons, astrocytes, pericytes and epithelial cells of the choroid plexus and, as we have recently demonstrated, in brain microvascular endothelial cells (BMECs). Knockout of a member of Pcdh subfamily, PcdhgC3, resulted in significant changes in the barrier integrity of BMECs. Here we characterize the endothelial PcdhgC3 knockout (KO) cells using paracellular permeability measurements, proliferation assay, wound healing assay, inhibition of signaling pathways, oxygen / glucose deprivation (OGD) and a pro-inflammatory cytokine tumour necrosis factor alpha (TNF treatment. PcdhgC3 KO showed an increased paracellular permeability, a faster proliferation rate, an altered expression of efflux pumps, transporters, cellular receptors, signaling and inflammatory molecules. Serum starvation led to significantly higher phosphorylation of extracellular signal-regulated kinases (Erk) in KO cells, while no changes in phosphorylated Akt kinase levels were found. PcdhgC3 KO cells migrated faster in the wound healing assay and this migration was significantly inhibited by respective inhibitors of the MAPK-, -catenin / Wnt-, mTOR- signaling pathways (SL327, XAV939 or Torin 2). PcdhgC3 KO cells responded stronger to OGD and TNF by significantly higher induction of interleukin 6 mRNA than wild type cells. These results suggest that PcdhgC3 is involved in the regulation of major signaling pathways and the inflammatory response of BMECs.